Antecedent and consequences of organizational identification: A study in the tourism sector of Sikkim - Deepak Subba (Future Business Journal, 2019)
Organizational identification has been identified as an important construct in behavioral research. It has been viewed from different perspectives such as marketing, organizational behavior, human resource management, and psychology. This study is conducted in organizational behavior context among the employees of tourism industry in Sikkim and gave some important contribution which can be useful to researchers and practitioners. With the application of social identity theory, the study investigated the antecedent and consequences of organizational identification. To test the research model, self-reports of 246 respondents are used and for analyzing data explorative factor analysis, confirmatory factor analysis and structural equation modeling were applied. Findings of the study suggested that perceived organizational support emerged as an antecedent of organizational identification, whereas job satisfaction and knowledge sharing behavior emerged as consequences of organizational identification.
Keywords: 650